EANM procedure guidelines for radionuclide therapy with 177Lu-labelled PSMA-ligands (177Lu-PSMA-RLT) - Kratochwil, Clemens; Haberkorn, Uwe (European journal of nuclear medicine and molecular imaging, 2019)
Prostate-specific membrane antigen (PSMA) is expressed in most prostate cancers and can be identified by PSMA-ligand imaging, which has already become clinically accepted in several countries in- and outside Europe. PSMA-directed radioligand therapy (PSMA-RLT) with Lutetium-177 (177Lu-PSMA) is currently undergoing clinical validation. Retrospective observational data have documented favourable safety and striking clinical responses. Recent results from a prospective clinical trial (phase II) have been published confirming high response rates, low toxicity and reduction of pain in metastatic castration-resistant prostate cancer (mCRPC) patients who had progressed after conventional treatments. Such patients typically survive for periods less than 1.5 years. This has led some facilities to adopt compassionate or unproven use of this therapy, even in the absence of validation within a randomised-controlled trial. As a result, a consistent body of evidence exists to support efficacy and safety data of this treatment. The purpose of this guideline is to assist nuclear medicine specialists to deliver PSMA-RLT as an “unproven intervention in clinical practice”, in accordance with the best currently available knowledge.